TINJAUAN PUSTAKA: FAKTOR RISIKO DAN DAMPAK BERAT BADAN LAHIR RENDAH (BBLR) - Amel Wahyu Maharani (Yayasan Pendidikan Medika Indonesia, 2024)
Low birth weight (LBW) is the condition of infants born with a body weight of <2500 grams. The rate of LBW in Indonesia has increased thus it is necessary to know the factors associated with the incidence of LBW to decrease the rate. This article is a literature review article that aims to determine the risk factors that contribute to the incidence of LBW and the impact caused by LBW. There are various factors that influence LBW that can be classified into maternal, fetal, and environmental factors. By identifying the risk factors for LBW and the impacts caused, it is expected that women, especially pregnant women, could avoid such factors in order to avoid the incidence of LBW in their children.